Instrumental motivation and Reading goals: Case study of Spanish L2 learners in Chile: La motivación instrumental y los objetivos de lectura: Estudio de caso de estudiantes de español como L2 en Chile - Soliman, Maha (Revista Interamericana de Investigación Educación y Pedagogía RIIEP, 2023)
Teaching-learning process involves reading texts to construct knowledge. In this context, a certain pedagogical goal is chosen to guide the reading and the way of interacting with texts. Somehow, this interaction used to be attributed to the intrinsic or internal motivation of the reader. However, instrumental motivation to learn a second language was not considered as an influential factor in reading assignments. Objective: Hence, the aim of this investigation is to explore the relationship between instrumental learning motivation and the reading goals of both the learner and the institution hosting the reading activity. Methodology: A qualitative case study has been applied and data were collected from four courses belonging to a Spanish L2 student exchange program in Chile during the first semester of 2019. Results: The results of Nvivo 12 analysis suggest that students learn Spanish for practical reasons that do not match with specific or complex reading content assigned in class by professors. Conclusion: Didactic material should engage students and be coherent with their language proficiency level to guarantee efficient learning process.